Perceived lesbian, gay, bisexual, and transgender (LGBT) supportive practices and the life satisfaction of LGBT employees: The roles of disclosure, authenticity at work, and identity centrality. Issue 3 (22nd January 2021) - Fletcher, Luke; Everly, Benjamin A.
Abstract : As an increasing number of lesbian, gay, bisexual, and transgender (LGBT) employees are choosing to disclose their LGBT identity at work, it is important to understand how organizations can best manage LGBT diversity in the workplace. Previous research has established that LGBT employees are more likely to derive benefits from working in organizations with supportive LGBT practices in place. However, the psychological mechanisms behind this process are largely unknown. The present research investigates the value of both disclosure and authenticity at work in understanding why perceptions of LGBT supportive practices facilitate the life satisfaction of LGBT employees. A time‐lagged questionnaire was completed by 150 LGBT individuals working in various UK organizations. Results of a path analysis find that although both disclosure and authenticity at work are positively related with LGBT supportive practices, it is the experience of authenticity at work which mediates the relationship between perceived LGBT supportive practices and life satisfaction. We also find that disclosure and authenticity at work are positively linked, yet LGBT identity centrality moderates this relationship. These findings show that authenticity at work may be particularly important for understanding the experiences of LGBT employees. Practitioner points: We measure perceptions of LGBT supportive practices and show evidence that such perceptions are positively related to important aspects of psychological well‐being. Authenticity adds value to disclosure at work as we find it is a key mediating process that translates LGBT supportive practices into increased life satisfaction. It seems that not disclosing is particularly detrimental for the authenticity for those whose LGBT identity is central to their self‐concept.